2022
DOI: 10.9734/ijecc/2022/v12i1131010
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Sucking Pests in Dual Season Cotton Ecosystem and Its Correlation with Weather Factors

Abstract: Population dynamics of sucking pests in cotton ecosystem were studied at Tamil Nadu Agricultural University, Coimbatore during winter (2021) and summer (2022) seasons. Weekly observations were recorded on 20 randomly selected plants representing top, middle and bottom canopy of the crop which was raised in regular planting dates of winter and summer and were maintained as per the recommended regular agronomic practices except insect management interventions. During winter season, sucking pests viz., leafhopper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Present results are corroborate with the findings of Sohrab et al [7] who observed two peaks during the crop growth period, 1 st peak at 30 DAS and 2 nd at 150 DAS with 11.65 and 26.83 aphids/leaf. Whereas Kiruthika et al [8] the highest aphid population was observed at 50DAS itself, during flowering stage of the crop with 18.7 adults / 3 leaves.…”
Section: Resultsmentioning
confidence: 81%
“…Present results are corroborate with the findings of Sohrab et al [7] who observed two peaks during the crop growth period, 1 st peak at 30 DAS and 2 nd at 150 DAS with 11.65 and 26.83 aphids/leaf. Whereas Kiruthika et al [8] the highest aphid population was observed at 50DAS itself, during flowering stage of the crop with 18.7 adults / 3 leaves.…”
Section: Resultsmentioning
confidence: 81%